Hubungan Pengetahuan Komunikasi Terapeutik terhadap Kemampuan Komunikasi Perawata dalam Melaksanakan Asuhan Keperawatan di Rumah Sakit Elisabeth Purwokerto - Diana RS,; Asrin,; Ekowati, Wahyu (Jurnal Keperawatan Soedirman, 2006)
Therapeutic communication is very important to construct the therapeutic relation of nursepatient and influences the improvement of quality of treatment service. Success of terapeutik communication is influenced by some factors such as lack of nurse's knowledge and ability to apply the therapeutic communication. The purpose of this study was to know the relationship between knowledge of therapeutic communication towards the nurse's communication ability in implementing the treatment upbringing in Elisabeth Hospital Purwokerto. The descriptive Research type of correlation. Population research is all nurses in Maria lodge of Elisabeth Hospital Purwokerto in the amount of 26 people, The research sample is taken from 23 people in according to the inclusive criteria. Data analysis method uses the distribution of frequency and statistic test "Spearman Rank". Result of research: Respondens of DIII in nursing are as much as 15 people (65,2%) and responders, who have education of SPK are as much as 8 people (34,8%). Responders, who have followed the training of therapeutic communication, are 18 people (78,3%) and 5 people (21,7%) not yet followed the training. The grade of knowledge about terapeutik communication is in good enough category (52,2%) and the least is in the unfavorable category (8.7%). The ability of therapeutic communication is in the good enough category (56,5%) and the least is in the unfavorable category (4,3%). The obtained result of statistic test using Spearman's rho is 0,636 and p 0,001. Conclusion: Most of the nurses are of DIII treatment and have followed the training of therapeutic communication. Nurses' knowledge and ability of therapeutic communication are in good enough category. There is a meaningful relation between knowledge of therapeutic communication and ability of therapeutic communication of the Elisabeth hospital nurses in implementing the treatment up bringing (p= 0,001). The strength of relation between the knowledge of therapeutic communication and ability of nurse's therapeutic communication Ni implementing/doing the treatment upbringing is in strong category (Spearman's rho 0,636).